Effect of Aeration Period and Co-Culture with Bacteria on Growth and Lipid Profile of Chlorella vulgaris - Khaq, Rizki Amalia Nurul; Rohman, Fatchur; Lukiati, Betty; Prabaningtyas, Sitoresmi (Biotropika: Journal of Tropical Biology, 2024)
Giving bacteria to microalgae culture can increase the growth of microalgae. Giving aeration can increase oxygen levels in the culture. Good culture conditions can optimize microalgae growth, so the biomass obtained is also higher. The amount of microalgae biomass is directly proportional to the amount of lipids produced. This study aims to determine the effect of the aeration period and the addition of potential bacteria on the growth and lipid profile of Chlorella vulgaris. The aeration periods were 6, 12, 18, and 24 hours. The bacteria used in the co-culture treatment of this study were indole acetic acid (IAA) producing bacteria, amylolytic bacteria, and nitrogen-fixing bacteria from the exploration and identification of several lakes in East Java. Microalgae C. vulgaris co-cultured with IAA, amylolytic and nitrogen-fixing bacteria were given aeration for 6 hours, 12 hours, 18 hours and 24 hours (in different treatment bottles). Microalgae treatment without giving bacteria is done only by giving aeration for 6 hours, 12 hours, 18 hours, and 24 hours (in different treatment bottles). The results showed that there was effect of the aeration period, the culture type, and the interaction between the aeration period and the addition of bacteria on the growth and lipid profile of C. vulgaris. The highest average cell density of C. vulgaris on day 16 was TBA18 mono-culture treatment with an aeration period of 18 hours (26.95 x 106 cells/mL), and BTA co-culture treatment without aeration (12.75 x 106 cells/mL). The harvested biomass of C. vulgaris was used for lipid profile assays. The results of the GC-MS test of TBA18 and BTA treatment showed that the two samples had the same six main compounds but different concentrations. The six compounds are oleic acid, palmitoleic acid, ?-linolenic acid, linoleic acid, stearidonic acid and myristic acid.